Análise dos marcadores de hemólise de concentrados de hemácias administrados por cateter central de inserção periférica - Mendes, Maria Teresa de Melo [UNIFESP] (2016)
Introduction: The occurrence of hemolysis in red blood cell (CH) during the transfusion process has been related to high shear stresses exerted by infusion systems and central catheters inserted peripherally (CCIP). Objectives: To identify variations in levels of hemolysis markers in CHs administered by PICC according to the diameter of the catheter; analyzing the variations in levels of hemolytic markers CHs administered according to PICC infusion rate; to evaluate the influence of the physical characteristics (height, pressure, exposure time and speed) present during the experiments, the variations in levels of hemolytic markers in CHs administered by PICC. Method: experimental study carried out in the laboratory under controlled temperature and humidity conditions. The sample consisted of aliquots of blood from 10 CHs bags with typing A +, infused by gravitational method CCIPs of 3French (Fr) and 4FR in free flow and two controlled speed. The experiments were divided into three stages: Basal, free flow and controlled flow. The degree of hemolysis, total and free hemoglobin, lactate dehydrogenase and potassium were analyzed in the process. Physical characteristics present during experiments with high pressure in the infusion system, exposure time and speed were evaluated. Continuous variables were described by mean, standard deviation, minimum, maximum and average values, being used paired t-test, t-test for independent samples and the Mann-Whitney test. Results: The sample consisted of 36 CHs aliquots from 10 CH bags, 12 randomized trials being carried out six in CCIP 3FR and six of 4FR. There was free hemoglobin average increase of 0.04 (p = 0.01) and the degree of hemolysis of 0.05 (p = 0.01) after infusion into free-flowing with an average elevation of the potassium 0.04 (p <0.01) and total hemoglobin decrease of 3.42 (p = 0.01) in controlled flow. The infused into CHs CCIPs of 4FR showed an average increase of the degree of hemolysis of 0.04 (p = 0.03) in free flow and the 0.059 potassium (P = 0.03) in controlled flow. CCIPs 3FR demonstrated significant mean increase in the degree of hemolysis (0.50; p = 0.03) and free hemoglobin of 0.03 (p = 0.01) at the selected speed. Comparatively, the gauges of CCIPs did not influence significant changes in markers of hemolysis. The minimum speed influenced average increase of 0.07 in the degree of hemolysis (p = 0.05) and maximum increased 0.04 (p = 0.01) The degree of hemolysis free hemoglobin and 0.02 (p < 0.01), with an average reduction of 4.34 of total hemoglobin (p = 0.04). Infusion pressure was positively correlated (p <0.05) with increased potassium. Conclusion: The calibers of the PICC do not alter the levels of markers of hemolysis, while controlling the infusion rate and the association between gauges of catheters and infusion rates were associated with erythrocyte trauma. The system time, infusion rate and exposure time had no effect on markers of hemolysis except for the infusion pressure which showed a positive correlation with the release of potassium during the controlled flow.